2019
DOI: 10.3390/ijms20061315
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteinases in Leishmania (Viannia) braziliensis Promastigotes Have Distinct Subcellular Distributions and Expression

Abstract: Serine proteinases in Leishmania (Viannia) braziliensis promastigotes were assessed in this work. This study included the investigation of the enzymatic activity of subcellular fractions obtained from benzamidine affinity chromatography, reverse transcription polymerase chain reactions, and in silico assays of subcellular localization of subtilisin. Promastigote serine proteinases showed gelatinolytic activity with molecular masses of 43 kDa to 170 kDa in the cytosolic fraction and 67 kDa to 170 kDa in the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The serine protease activity measured by Z-FR-AMC, a substrate for serine proteases such as cathepsins, kallikrein and plasmin (41), was relatively the same among promastigotes and axenic amastigotes. Serine enzymatic activity is generally con rmed by using PMSF, AEBSF and TLCK inhibitors (26). Besides, PMSF and AEBSF are known to inhibit a broad range of serine proteases including subtilisins while TLCK has a greater preference for Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The serine protease activity measured by Z-FR-AMC, a substrate for serine proteases such as cathepsins, kallikrein and plasmin (41), was relatively the same among promastigotes and axenic amastigotes. Serine enzymatic activity is generally con rmed by using PMSF, AEBSF and TLCK inhibitors (26). Besides, PMSF and AEBSF are known to inhibit a broad range of serine proteases including subtilisins while TLCK has a greater preference for Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, based on the previous role seen for subtilisins as maturases of TXNPx (18,26), our study examined the expression of subtilisin transcripts from SB clan and S8 family (LbrM.13.0860 and LbrM.28.2570) and TXNPx (LbrM.15.1080). In general, almost all isolates (promastigotes and axenic amastigotes) expressed the three mentioned genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that L. (Viannia) braziliensis promastigotes express serine proteinases that have distinct subcellular distributions and expression. Taken together, this might contribute to the maintenance of this parasite’s lifestyle at physiological pH, in the cytosol and on the external face of the parasitic membrane [ 134 ]. In stark contrast, the proteinases secreted from the host also affect the dynamics and progression of the infection, in addition to the development of the lesion [ 135 ].…”
Section: Virulence Factors Of Leishmaniamentioning
confidence: 99%
“…In this concern, OPB facilitates the establishment of the infection of murine macrophages by L. (L.) donovani [ 144 ], while it is associated with maintaining the infection of murine macrophage in L. (L.) major [ 145 ]. A recent study proposed that promastigotes of L. (V.) braziliensis express SPs that contribute to the maintenance of this parasite’s lifestyle at physiological pH and the out membrane of the parasite [ 134 ]. Taken together, odorant-binding protein (OBP) regulates the degradation of enolase–plasminogen complexes of the parasite, immune evasion, and disease pathology [ 144 ].…”
Section: Virulence Factors Of Leishmaniamentioning
confidence: 99%